Anthropology of the Middle East and North Africa : Into the New Millennium - Slyomovics, Susan; Hafez, Sherine (Book collections on Project MUSE., 2013)
This volume combines ethnographic accounts of fieldwork with overviews of recent anthropological literature about the region on topics such as Islam, gender, youth, and new media. It addresses contemporary debates about modernity, nation building, and the link between the ideology of power and the production of knowledge. Contributors include established and emerging scholars known for the depth and quality of their ethnographic writing and for their interventions in current theory.